Evaluasi Penatausahaan Barang Milik Daerah di Badan Pengelolaan Keuangan Kabupaten Aceh Singkil - Poedjianto, Arief; Warjio, Warjio; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2019)
This study aimed to evaluate the administration of property in the area of Financial Management Agency of Aceh Singkil Regency which has the function of asset management area. This study used qualitative research methods. Observation is the participation of the data collection methods used to collect research data. The survey results revealed that the evaluation of the procedure of administration of fixed assets, including: accounting, inventory and reporting as well as the completeness of the card inventory of goods, gained an average level of suitability administration of fixed assets for the Government of Aceh Singkil Regency is 57%, which means the administration of fixed assets for the Government Aceh Singkil meet enough criteria in accordance with Regulation No. 19 Year 2016. The obstacles faced in the administration of fixed assets are (1) The lack of work ethic and discipline of user goods (2) The limited data of supporting fixed assets, (3) Lack of education and training related to the management of local goods, (4) The low coordination and commitment of the parties involved in the administration of the fixed assets, and (5) No use of applications in the recording of local goods.Â